Ovarian cystadenofibroma: A masquerader of malignancy - Wasnik, Ashish (Medknow Publications, 2010)
Ovarian cystadenofibroma is a relatively rare benign ovarian tumor that contains both epithelial and fibrous stromal components. The appearance of cystadenofibroma on imaging is often complex; cystic- to solid-appearing masses may be visualized and it often resembles a malignant tumor. Owing to the fibrous component of this tumor, MRI shows low-signal intensity on T2W images. This finding may help a radiologist make a preoperative diagnosis of this tumor and thus perhaps avoid aggressive surgical management.